A Comparison between Inferior Alveolar Nerve Block and Crestal Anesthesia in Children Undergoing Dental Extraction Procedure - Fatemeh Sadat Sajadi; Parnian Poureslami; Saeed Hajmohammadi; Behdad Saeedi; Jelveh Hasheminejad (Association of Support to Oral Health Research (APESB), 2023)
Objective: To evaluate the efficacy of crestal anesthesia compared to the inferior alveolar nerve block (IANB) in 6-9-year-old children undergoing tooth extraction. Material and Methods: This case-control study was conducted on 70 children who needed bilateral mandibular primary molar extractions. The Faces Pain Scale was used to determine the efficacy of the anesthetic technique. Demographic data, onset time of anesthesia, duration of anesthesia, and blood pressure were also recorded. The data were analyzed using SPSS 25 and analytical tests: t-test, chi-squared test, and one-way ANOVA. The level of significance was set at p<0.05. Results: The efficacy of the IANB was significantly higher than the crestal anesthesia (p<0.05). The duration of IANB anesthesia was significantly more than the crestal anesthesia (p<0.05). The two anesthetic techniques showed no significant differences in pediatric blood pressure as a determinant of the pain evoked in children during the injection (p>0.05). Conclusion: Crestal anesthesia proved an effective method to extract primary molars. However, further studies are necessary to confirm this.